Contemporary Profile and In-Hospital Outcomes of Decompensated Heart Failure in a Semi-Rural Setting in Cameroon: The Buea Heart Study - Clovis Nkoke; Jean Jacques Noubiap; Siddikatou Djibrilla; Ali Abas; Ahmadou Musa Jingi; Ulrich Flore Nyaga; Gijo Thomas; Alain Menanga; Samuel Kingue; Anastase Dzudie (Global Heart)
Background: Available evidence suggests that the epidemiology of heart failure (HF) in sub-Saharan Africa (SSA) might be changing. However, there is a scarcity of contemporary data on the epidemiology and prognosis of hospitalized HF patients in Cameroon despite improvements in the treatment of HF and the changing epidemiology of HF in SSA in the last decade. Objective: To examine the contemporary characteristics, the in-hospital outcomes, and their predictors in patients hospitalized for decompensated HF in Buea, South West region of Cameroon. Methods: We conducted an observational prospective cohort study. We included consecutive patients hospitalized for HF from March 2021 to March 2024. Multivariate logistic regression analyses were performed to determine factors associated with in-hospital mortality and prolonged length of hospital stay (LOS). A p-value < 0.05 was considered statistically significant. Results: Out of the 477 patients included, 254 (53.2%) were females. The mean age was 60.3 ± 16.5 years. The most common co-morbidities were hypertension (55.6%), atrial fibrillation (20.8%), diabetes mellitus (17.6%), and chronic kidney disease (14.1%). The most common causes of heart failure were hypertensive heart disease (41.7%), ischemic heart disease (15%), cor pulmonale (11.9%), and dilated cardiomyopathy (9%). The median length of stay (LOS) was seven days. Factors that increased odds of prolonged LOS were atrial fibrillation (OR = 2.04, CI: 1.26–3.35; p = 0.005). Factors that reduced odds of prolonged LOS were valvular heart disease (VHD) (OR = 0.49, CI: 0.26–0.91; p = 0.023), systolic blood pressure (SBP) (OR = 0.99 per 1 mmHg increment, CI: 0.98–0.99; p = 0.005), and natremia (OR = 0.96 per 1 unit increment, CI: 0.93–0.99; p = 0.010). In-hospital mortality was 11.9%. Factors that increased odds of in-hospital mortality were VHD (OR = 2.40, CI: 1.02–5.64; p = 0.045) and dobutamine administration (OR = 4.37, CI: 1.11–17.16; p = 0.034). Factors that reduced odds of mortality were SBP (OR = 0.99, CI = 0.98–0.99; p = 0.033), natremia (OR = 0.93, CI: 0.89–0.97; p < 0.001), and glomerular filtration rate (OR = 0.98 per 1 unit increment, CI: 0.97–0.99; p = 0.001). Conclusion: The causes of HF are still predominantly hypertensive, but there is an increasing contribution of ischemic heart disease. There is a need to improve hypertension control and other risk factors for ischemic heart disease in SSA.